Measuring activities of multinational enterprise groups via large cases units - Mushtaq Hussain; Rami Peltola; Sanjiv Mahajan (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2019)
MNE groups stand at the centre of economic globalisation. They play a very important role cutting across most economies in the world. This paper presents the rationale, and the recommendation, as to why national statistical institutes (NSIs) should establish a team of experts (also named large cases unit - LCU) to deal with all statistical aspects of MNE groups in economies where such MNE groups are significant. The main objective of an LCU is to provide all relevant statistical domains with consistent data originating from the biggest MNE groups for compiling their statistics. This can be ensured by collecting timely and accurate data for MNE groups at the very beginning of the production process of economic statistics, enabling a prompt reaction to data changes and the resolution of anomalies before they are processed by any of the statistical domains. The paper argues that in an ever-changing globalised world, investment in an LCU-type entity is essential to ensure that national statistics are of high quality and do not double-count or miss any activity.
Keywords: E01; F62; 330; LCU; economic globalisation; consistency